2010
DOI: 10.1002/jbmr.310
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate cyclase and calmodulin-dependent kinase have opposite effects on osteoclastogenesis by regulating the PKA-NFATc1 pathway

Abstract: Nuclear factor of activated T cells c1 (NFATc1) is a transcription factor crucial for the differentiation of osteoclasts. In this study we discovered new signaling pathways involving cAMP regulators that modulate NFATc1 during osteoclastogenesis. The osteoclast differentiation factor receptor activator of NF-kB ligand (RANKL) increased the expression of adenylate cyclase 3 (AC3), accompanied by a rise in the intracellular cAMP level in osteoclasts. The knockdown of AC3 enhanced in vitro osteoclastogenesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 34 publications
0
42
2
Order By: Relevance
“…Wnt3a can also trigger the cAMP/PKA pathway[43], which could suppress osteoclast differentiation by PKA-mediated phosphorylation and inactivate the nuclear factor of activated T-cells 1 (NFATC1)[44]. …”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…Wnt3a can also trigger the cAMP/PKA pathway[43], which could suppress osteoclast differentiation by PKA-mediated phosphorylation and inactivate the nuclear factor of activated T-cells 1 (NFATC1)[44]. …”
Section: Wnt Signaling Pathwaymentioning
confidence: 99%
“…(22) Bone marrow culture, osteoclast differentiation, and TRAP staining Bone marrow cells were isolated by flushing the bone marrow space of femur and tibia of 6-week-old Tie2-Dkk1 TG and WT mice. (23) Cells were incubated with a modified essential medium (a-MEM) containing 10% fetal bovine serum overnight on culture dishes. Nonadherent cells were collected and treated with macrophage colony-stimulating factor (M-CSF; 20 ng/mL) for 3 days on noncoated Petri dishes.…”
Section: Analysis Of Bone Histomorphometrymentioning
confidence: 99%
“…BMMs were seeded in 48-well plates (2 Â 10 4 cells/well) and cultured for 5 days with 30 ng/mL of M-CSF and 100 ng/mL of RANKL to induce osteoclast differentiation. (23) The cells were fixed in 3.7% formaldehyde for 10 minutes, permeabilized with 0.1% Triton X-100 for 1 minute, and stained with the leukocyte acid phosphate assay kit (Sigma, St. Louis, MO, USA) to detect tartrate-resistant acid phosphatase (TRAP) activity. (3,23) The surface area of TRAP-stained multinuclear osteoclasts that contained three or more nuclei were measured by the Osteomeasure system.…”
Section: Analysis Of Bone Histomorphometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Gsα deletion in osteogenic lineage cells expressing osterix and col1a has demonstrated that Gsα plays important roles during skeletal development by regulating mesenchymal cell commitment, osteoblast differentiation, and mineralization without affecting osteoclast function6789. Recent studies have also suggested that cAMP levels are regulated by several mechanisms including Wnt signaling, adenylyl cyclase, and Ca 2+ /Calmodulin-dependent kinases to delicately control osteoclastogenesis1011. In addition, in fibrous dysplasia, a clinical condition in which activating Gsα mutations cause elevated cAMP levels, increased osteoclasts occur primarily in response to osteoblast secretion of interleukin-61213.…”
mentioning
confidence: 99%